2010
DOI: 10.1002/jsfa.4082
|View full text |Cite
|
Sign up to set email alerts
|

Increasing water productivity on Vertisols: implications for environmental sustainability

Abstract: Based on the results, the study concluded that surge and deficit irrigation technologies not only improve water productivity but also enhance environmental sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…Based on the farmers' report, a seasonal total of 781 mm irrigation depth was applied to maize (RB) and about 168 mm was applied to the barley field (LB). This corroborates the work of Jiru and Van Ranst () who reported that farmers applied a seasonal irrigation depth of 711–722 mm to the maize crop grown in the area. The irrigation amount indicates that there was a relatively excess application to maize in RB and limited application to barley in LB, which was a result of relatively higher canal water flow to RB whereas limited canal water flow was provided to LB in the 2013/2014 irrigation season.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Based on the farmers' report, a seasonal total of 781 mm irrigation depth was applied to maize (RB) and about 168 mm was applied to the barley field (LB). This corroborates the work of Jiru and Van Ranst () who reported that farmers applied a seasonal irrigation depth of 711–722 mm to the maize crop grown in the area. The irrigation amount indicates that there was a relatively excess application to maize in RB and limited application to barley in LB, which was a result of relatively higher canal water flow to RB whereas limited canal water flow was provided to LB in the 2013/2014 irrigation season.…”
Section: Resultssupporting
confidence: 91%
“…Comparison of potential CWP for the three strategies against the baseline revealed that the highest CWP (1.8 and 1.6 kg m ‐3 ) was obtained under IV and III for maize and (1.3 kg m ‐3 ) under III for barley (Figure ). The result also corroborates the findings of Jiru and Van Ranst () who reported grain CWP values ranging between 0.5 and 1.7 kg m ‐3 for maize based on a field experiment conducted in the same area.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Al-Said et al (2012) show the effect of drip versus sprinkler irrigation on vegetable yield in Oman, showing that the yield per unit of irrigation water applied is higher for drip irrigation. The effects of irrigation strategies such as deficit or supplementary irrigation on ET and Y were studied by different scholars (Igbadun et al, 2012;Qiu and Meng, 2013;Jiru and Van Ranst, 2010;Bakhsh et al, 2012;Jinxia et al, 2012). In a literature review, Geerts and Raes (2009) point out that deficit irrigation strategy decreases the consumptive water use per unit of yield compared to full irrigation.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Al-Said et al (2012) show the effect of drip versus sprinkler irrigation on vegetables yield in Oman, showing that the yield per unit of irrigation water applied is higher for drip irrigation. The effect of irrigation strategies such as deficit or supplementary irrigation on ET and Y were studied by different scholars Qiu and Meng, 2013;Jiru and Van Ranst, 2010;Bakhsh et al, 2012;Jinxia et al, 2012). In a literature review, Geerts and Raes (2009) point out that deficit irrigation strategy decreases the consumptive water use per unit of yield compared to full irrigation.…”
Section: Introductionmentioning
confidence: 99%